Influence of rosuvastain on the lipid profile and inflammatory markers in patients with gout and arterial hypertension - Zolotariova, N. A.; Romanchenko, M. I. (Journal of Education, Health and Sport, 2017)
Currently there is scarce data on lipid-lowering effects of rosuvastatin in rheumatologic pathology, moreover there are no current studies of its anti-inflammatory activity in patients with gout comorbid with arterial hypertension (AH). The purpose of this study is to investigate the lipid-lowering and anti-inflammatory effect of combination therapy with the addition of rosuvastatin in patients with gout AH. We measured and compared the level of total cholesterol, TG, LDL, VLDL, HDL, atherogenic index (AI) as well as biochemical parameters of inflammation (ESR, C-reactive protein, sialic acids, seromucoid and fibrinogen-A in 30 patients (29 male, 1 female) with gout + AH, the observation period was 43 ± 9 days. The study showed decrease in total cholesterol by 29,2% to 3,88 ± 0,78 mmol/L (p<0,0001), decrease in triglycerides by 23,91% to 1,40 [1,12 – 1,94] mmol/L (p=0,01), LDL decrease by 36,95% to 1,86 ± 0,51 mmol/L (p<0,0001), normalizing in 86,67% of patients, no effect on HDL, remaining at a level of 1,23 mmol/L and significant normalization of atherigenic index decreasing to 2,23 ± 0,83 (-30,53%, p<0,0001). Inflammation markers showed significant positive dynamics: ESR significantly decreased to 15,90 ± 9,33 mm/h (p <0,0001), the level of C-RP reached a normal value of 1,34 [0 – 6,0] mg/ml (p = 0,0007), and the concentration of sialic acid and seromucoid decreased and reached the upper limit of the norm (202,33 ± 44,0 at p=0,07 and 5,0 ± 1,25 U at p=0,004 respectively). This study shows that standard therapeutic complex with the addition of rosuvastatin at a dose of 10 mg/day leads to a statistically significant normalization of the average levels of total cholesterol, triglycerides, LDL and VLDL and atherogenic index, causing no effect on the level of HDL. Additionally this treatment leads to significant normalization of the levels of C-RP, seromucoid and sialic acids, as well as statistically significant, but not reaching the normal values reduction of ESR and fibrinogen-A, indicating the anti-inflammatory effect of this therapeutic complex.